2020
DOI: 10.1111/jan.14577
|View full text |Cite
|
Sign up to set email alerts
|

Ageing simulation in health and social care education: A mixed methods systematic review

Abstract: Aim To identify, evaluate and summarize evidence from qualitative, quantitative and mixed method studies conducted using age suits or other age simulation equipment, with health and social care students. Design Convergent segregated mixed method review design as outlined by the Johanna Briggs Institute. Data Sources CINAHL (+ with Full Text), MEDLINE, PsycINFO, PubMed, SocINDEX, Web of Science, Cochrane Library, Emerald Insight, Proquest nursing, Science Direct, Wiley Online and BioMed Central (January 2000–Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 55 publications
0
38
0
Order By: Relevance
“…Target populations predominantly included student groups in health-related professions; outcomes represented the areas of better understanding of what aging means, empathy with older adults, and attitudes toward older adults. Two recent review articles ( Eost-Telling et al, 2020 ; Bowden et al, 2021 ) have targeted these psychological outcomes of age simulation in a broader approach by including variations of interventions that either used a “full” ASS, only single components (i.e., only goggles), or aging games including role-play instructions. In this study, we use the ASS as an age simulation intervention able to provide first-hand experiences of the motor-sensory deficits associated with advancing age for our participants (see also the definition of age simulation intervention in Bowden et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Target populations predominantly included student groups in health-related professions; outcomes represented the areas of better understanding of what aging means, empathy with older adults, and attitudes toward older adults. Two recent review articles ( Eost-Telling et al, 2020 ; Bowden et al, 2021 ) have targeted these psychological outcomes of age simulation in a broader approach by including variations of interventions that either used a “full” ASS, only single components (i.e., only goggles), or aging games including role-play instructions. In this study, we use the ASS as an age simulation intervention able to provide first-hand experiences of the motor-sensory deficits associated with advancing age for our participants (see also the definition of age simulation intervention in Bowden et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In their review, Bowden et al (2021) identified mainly positive effects of aging simulations on knowledge, empathy levels, and attitudes towards older adults among younger healthcare professionals. Similarly, Eost-Telling et al (2020) focused on health and social care students and concluded that effects of such aging simulation interventions on attitudes towards older people were predominantly positive. Although both reviews concluded that such ASS interventions might be useful, for example to promote person-centered care, they also found large heterogeneity in the methodological quality among included studies.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical simulation includes a wide range of methods and techniques that allow students to practice clinical skills before using them in relation with real patients [ 16 ]. The main purpose of using simulation in health care is to prepare students to face real situations that increase help-seeker safety, reduce errors and improve nurses’ clinical judgments [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In additon to this they stated that participant feedback showed that the this intervention increased empathy and awareness about geriatric nursing (12). In a recent systematic review, Eost-Telling et al, (2021) stated that aged simulation equipments/suits can have a positive effects on students' attitudes and empathy towards older adults (13). Rueffort and Bullinger (2020) examined whether wearing an age simulation suit would make a sensitization compared to participants observing the intervention.…”
Section: Introductionmentioning
confidence: 99%
“…It also stated that this experience allowed them to put themselves in the shoes of older adults and to experience age-related difficulties (6). The recent studies have been made to change nursing students' attitudes towards the elderly (11)(12)(13). But the studies on changing the attitudes of nurses who work actively with the elderly (geriatric care nurses) towards the elderly are limited.…”
Section: Introductionmentioning
confidence: 99%